2019
DOI: 10.3390/min9090511
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Methods Using Calcium-Containing Ores for Fluoride Removal in Wastewater

Abstract: F-containing wastewater does great harm to human health and the ecological environment and thus needs to be treated efficiently. In this paper, the new calcium-containing precipitant calcite and aided precipitant fluorite were adopted to purify F-containing wastewater. Relevant reaction conditions, such as reaction time, oscillation rate, dosage of hydrochloric acid, calcite dosage and the assisting sedimentation performance of fluorite, and action mechanism are analyzed. The experiment showed that the removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…As the aforementioned fluoride-originated pollutants raise several health problems, the World Health Organization (WHO) determined the acceptable level of fluoride content in drinking water at the level of 1.5 mg/L [ 45 ]. However, the concentration of fluorides in industrial wastewater mostly exceeds these WHO guidelines, reaching even thousands of milligrams per litre [ 40 , 84 , 85 ]. Thus, fluoride pollution in the aquatic environment, caused by natural and artificial activities, has been a significant problem worldwide.…”
Section: Anthropogenic Sources Of Contamination With Fluorine Compoundsmentioning
confidence: 99%
“…As the aforementioned fluoride-originated pollutants raise several health problems, the World Health Organization (WHO) determined the acceptable level of fluoride content in drinking water at the level of 1.5 mg/L [ 45 ]. However, the concentration of fluorides in industrial wastewater mostly exceeds these WHO guidelines, reaching even thousands of milligrams per litre [ 40 , 84 , 85 ]. Thus, fluoride pollution in the aquatic environment, caused by natural and artificial activities, has been a significant problem worldwide.…”
Section: Anthropogenic Sources Of Contamination With Fluorine Compoundsmentioning
confidence: 99%
“…Incident of crippling fluorosis, thyroid disorder, infertility in women, cancer, and Alzheimer's syndrome Different processes have been evaluated to reduce high fluoride concentrations in water and, consequently, to prevent hazardous health effects. Some examples of examined technologies include adsorption [11][12][13], chemical precipitation using lime or magnesium salts [14,15], co-precipitation and adsorption through coagulation-flocculation with alum [16,17], ion exchange [18,19], electrodialysis [20][21][22], and electrocoagulation [23,24]. Amongst these technologies, electrocoagulation (EC) has emerged in recent decades as a suitable alternative compared to the conventional coagulation process.…”
Section: Fluoride Concentration (Mg L 1 )mentioning
confidence: 99%
“…For a continuous reactor, Rosales et al [87] indicated that residual fluoride concentration had a linear trend with flow rate at 6 A cm −2 ; in contrast, such trend was not observed for 4 A cm −2 and 8 A cm −2 due to the interferences with co-existing ions. Considering Equation (15), current density also affects energy consumption leading to an increase in operating costs. Rosales et al [87] reported that the energy consumption increased (36.78, 93.87, 160.83 kWh m −3 ) by an increase in current density (4, 6, 8 mA cm −2 ); it was confirmed that for each current density increasing in flow rate (decrease in retention time) caused the reduction of energy consumption.…”
Section: Current Densitymentioning
confidence: 99%
“…Jiang and Zhou studied the effect of aluminum on the treatment of fluorinecontaining synthetic wastewater by crystallization [8]. Wang et al [9] demonstrated the effectiveness of calcium-containing precipitant calcite together with added precipitant fluorite to purify F-containing wastewater.…”
Section: Introductionmentioning
confidence: 99%